แนวคิดการจัดคนให้เหมาะสมกับงานและการแบ่งงานในบริบทที่แตกต่างกัน แนวคิดนี้ยังคงใช้ได้หรือไม่ในยุคสมัยใหม่ และหลังสมัยใหม่ - เหลืองภิรมย์ นพดล (RMUTSB ACADEMIC JOURNAL, 2013)
ประวัติศาสตร์การบริหารได้วิวัฒนาการมาคู่ขนานกับการสร้างองค์กรขนาดใหญ่ อาทิ อาณาจักรโรมัน อียิปต์ จวบจนปัจจุบัน ใน คลาสสิก ราวปี ค.ศ. 1900 มนุษยชาติได้ทุ่มเทความพยายามมหาศาลในการพัฒนาองค์กรเพื่อแก้ปัญหาความไร้ประสิทธิภาพที่มนุษย์ต้องเผชิญ แนวคิดเหตุผลนิยม การจัดการ และหลักการควบคุม ถูกนำมาใช้ในการแก้ปัญหาเหล่านี้ อาทิ แนวคิดการจัดคนให้เหมาะสมกับงานที่อ้างอิงมาจากแนวคิดการแบ่งงาน และหลักการวิธีที่ดีที่สุดที่เทย์-เลอร์ ได้กล่าวไว้ใน ปี ค.ศ. 1911 อย่างไรก็ตาม เฮนรี ฟาโยล (ค.ศ.1841-1925) วิศวกรชาวฝรั่งเศส ได้เสนอแนวคิด “หลักการบริหารทั่วไป” ระบุว่าการจัดคนให้ถูกตำแหน่งต่างๆ ไม่ได้มีความหมายเหมือนกับแนวคิดการจัดคนให้เหมาะสมกับงานย่อยๆ ของเทย์เลอร์ เน้นการแบ่งงานตามหน้าที่มากกว่าเป็นการจัดคนให้เหมาะสมกับงาน การแบ่งงานได้พิสูจน์แล้วว่าได้ส่งผลกระทบต่อการจำกัดความสามารถของมนุษย์ในการพัฒนาทักษะอื่นๆ เกิดความซ้ำซากในการทำงานนำไปสู่ความเบื่อหน่ายในการทำงาน ในขณะที่การแบ่งงานตามหน้าที่ ไม่ทำให้เกิดความเบื่อหน่ายในการทำงาน แต่ส่งผลให้เกิดการทำงานเป็นทีมและส่งเสริมความเป็นประชาธิปไตยในการแบ่งปันปริมาณงาน ในยุคหลังสมัยใหม่ไม่เชื่อว่าจะมี “วิธีที่ดีที่สุด” จากการแบ่งงานตามความถนัด หรือ การแบ่งงานย่อยๆ แต่เชื่อในแนวทางในการสร้างทีมงานที่มีจิตวิญญาณที่ดีที่สุด ดังนั้นในยุคหลังสมัยใหม่ การจัดทีมงานที่มีจิตวิญญาณที่ดีที่สุดให้ได้ทำงานในสภาวะที่ถูกต้อง น่าจะเหมาะสมกว่าการจัดคนแต่ละคนให้เหมาะสมกับงานย่อยๆ ในยุคสมัยใหม่ Put the right man to the right job and division of labor concept in different context : Is it still valid in Modernity and Post-modernity era History of Management had evolved in paralell of the building of the large organization i.e. Roman and Egypt empire until to now a day. In classical era around 1900, obviously human put lots of efforts to develop the organization to resolve the poor efficiency problems which they have faced. rationalism, management and controlling principle emerged to resolve these problems. The concept of “Put the right man to the right job” was intrepreted in different ways. In classical era, “Put the right man to the right job” was referred to the specialization and “one best way” principle as mentioned by F. Talor in 1911. However Henri Fayol (1841-1925), french engineer proposed the “ General Principles of Management “. He coined the “Put the right man to the right palce” which was not referred to the specialization and one best principle but the appropriateness of the Job Function within the management team. The concept : “Put the right man to the right job or place” of F.Taylor and H.Fayol is totally different according to the management principle. Fayol focused to the division of work rather than the division of labor. Division of the Labor has been proven to create the deskill problems of the worker while the division of work was not. The Division of work also promote the team work and the spirit of democracy to share the work load. In postmodernity era, it was believed this is no “One best way” by mean of the specialization or division of Labor but “One best spirited team” . Therefore “ Put the right spirited team to the right job and condition” in Postmodernity era should be more appropriate than “Put the right man to the right job” in modernity era.